Pathogenic intronic splice-affecting variants in MYBPC3 in three patients with hypertrophic cardiomyopathy - Wood, KA; Ellingford, JM; Eden, J; Thomas, HB; O'Keefe, RT; Hopton, C; Newman, WG (MDPI, 2021)
Genetic variants in MYBPC3 are one of the most common causes of hypertrophic cardiomyopathy (HCM). While variants in MYBPC3 affecting canonical splice site dinucleotides are a well-characterised cause of HCM, only recently has work begun to investigate the pathogenicity of more deeply intronic variants. Here, we present three patients with HCM and intronic splice-affecting MYBPC3 variants and analyse the impact of variants on splicing using in vitro minigene assays. We show that the three variants, a novel c.927-8G>A variant and the previously reported c.1624+4A>T and c.3815-10T>G variants, result in MYBPC3 splicing errors. Analysis of blood-derived patient RNA for the c.3815-10T>G variant revealed only wild type spliced product, indicating that mis-spliced transcripts from the mutant allele are degraded. These data indicate that the c.927-8G>A variant of uncertain significance and likely benign c.3815-10T>G should be reclassified as likely pathogenic. Furthermore, we find shortcomings in commonly applied bioinformatics strategies to prioritise variants impacting MYBPC3 splicing and re-emphasise the need for functional assessment of variants of uncertain significance in diagnostic testing.